Analysis of Islamic Law on the Mangngade Tradition in Mattampawalie Village Lappariaja District Bone Regency - Herman; Sastrawati, Nila; Asni (International Journal of Islamic Studies, 2024)
Mangngade or carrying out customs is a community activity in Mattampawalie Village, Lappariaja District, Bone Regency which is carried out every year in December and January. The problems raised in this study, namely how the process of the manggade ceremony is, and the factors that encourage people to work on the mannggade tradition, as well as the values ​​of Islamic law in the mannggade tradition. There are three stages in the manggade procession, namely mabbaji-baji (the process of cleaning the ritual place), mannggade sokko, mannggade beppa (cake). In mannggade the community performs prayers related to agriculture, in order to avoid natural disasters, gain peace, safety and success in personal life. The data collection methods used are ethnographic methods, archaeological data recording, and documentation. The results of observations, interviews, and data observations were then analyzed using concepts in Islamic culture and law. Based on these data, it was finally concluded that mannggade is one of the traditions that are still carried out by the people of Mattampawalie Village from generation to generation from their ancestors in building recognition of the existence of their group.